Amino acids profiling and transcriptomic data integration demonstrates the dynamic regulation of amino acids synthesis in the leaves of Cyclocarya paliurus - Du, Zhaokui; Lin, Weida; Zhu, Jinxing; Li, Junmin (PeerJ, 2022)
Background Cyclocarya paliurus is a tree well known for its edible and medicinal leaves. Amino acids are essential nutritional components that are present in foods and closely related to the flavor and quality of tea. However, the abundance of amino acids and the regulation of amino acid biosynthesis in the leaves of C. paliurus have not been investigated across different developmental stages. Methods A combined metabolomic and transcriptomic analysis was employed to investigate the changes in the amino acid profile over several developmental stages (S1, the smallest fully expanded leaf; S3, full leaf enlargement and full leaf thickness; and S2, an intermediate developmental stage between S1 and S3) and the molecular mechanism was elucidated. Results The results showed that leaves at the S1 stage had the highest content, while those at the S3 stage had the lowest content of amino acids; fourteen differentially expressed genes were involved in the glycolysis pathway, the tricarboxylic acid cycle and the pentose phosphate pathway, which indicated that the reduced abundance of amino acids in the leaves of C. paliurus (mature leaves) may be attributable to reduced gene expression related to carbohydrate metabolism. Four basic leucine zipper transcription factors might play important roles in the regulation of the biosynthesis of amino acids in the leaves of C. paliurus. Conclusions Leaves at the S1 stage are recommended for high quality tea production because of their high content of amino acids, while leaves at the S2 stage are recommended for generous tea production because of their high levels of sweet flavor amino acids (alanine) and essential amino acids (methionine, phenylalanine, threonine, and tryptophan).
Keywords: Cyclocarya paliurus; Amino acids; Developmental stages; Tea; Metabolomics; Transcriptomics